Flexible ureteroscopy, extracorporeal shock wave lithotripsy and mini percutaneous nephrolithotomy for management of lower pole renal hard stones ≤ 2 cm: a prospective randomized study - Khaled Magdy Zeinelabden; Elsayed Abdelhalim; Mohamed Galal; Tarek Abdelbaky; Hossam Nabeeh (BMC Urology)
Abstract Background Managing lower pole renal stones presents clinical challenges influenced by various factors such as stone size, location, and density. This study aims to assess the efficacy, safety, and stone-free rates of Flexible Ureteroscopy (FURS), Extracorporeal Shock Wave Lithotripsy (ESWL), and Mini Percutaneous Nephrolithotomy (Mini PCNL) for treating lower pole renal hard stones (< 2 cm). Methods A prospective single-centre comparative study was conducted on 414 adult patients with primary lower pole renal hard stones. Patients were evenly distributed into three groups: Flexible Ureteroscopy (FURS) utilizing holmium laser lithotripsy, Extracorporeal Shock Wave Lithotripsy (ESWL), and Mini PCNL employing holmium laser lithotripsy. Results Statistically significant differences with P value < 0.001 were observed among groups in stone-free rates, hospital stay, radiation exposure, operative duration, auxiliary treatments, and overall cost. No statistically significant differences were found in demographic data with P value = 0.245 or complication rates with P value = 0.611 among the groups. At the 2-week follow-up, stone-free rates were 90.2% for Flexible Ureteroscopy which was comparable with mini PCNL and both were significantly higher than ESWL 61.5%. Conclusions Mini PCNL and Flexible URS demonstrated comparable stone-free rates for moderate-sized, hard lower pole renal stones, surpassing ESWL. However, Mini PCNL showed longer operative times, increased radiation exposure, and elevated risks of complications and morbidity compared to Flexible URS. Considering these factors, Flexible URS might be recommended in those types of stones. Trial Registration Our study has been approved by local ethical committee Kafrelsheikh university (KFSIRB20069) on 30/10/2023 and by clinical trials (NCT06120257) on 15/12/2023.